POLYVINYL CHLORIDE PROCESSING IN A CYCLICAL ECONOMY - САВЧУК, АНДРІЙ; СОВА, НАДІЯ (Technologies and Engineering, 2024)
Purpose. Determining the current state of PVC waste processing and finding ways to adapt PVC processing technologies to the current requirements of the circular economy. Methodology. The methods of literary and systematic analysis of scientific publications on the subject of the study and generalization of the obtained research results were used. Findings. The article considers the state of the art of PVC materials use and waste recycling in the world. The existing methods of producing polyvinyl chloride are analyzed and the possible applications of each type of typical formulation are presented. The main formulations of PVC compositions for the manufacture of rigid and soft products are considered. The influence of different types of additives on the performance properties of PVC products is described. The existing methods of processing PVC compositions into finished products are analyzed. Statistical data on the areas of application of PVC products in different countries are presented. A detailed analysis of the sources of polyvinyl chloride waste generation is carried out and their main characteristics are presented. The existing methods of processing various types of PVC waste are systematized. The advantages and disadvantages of existing technologies are analyzed. Modern approaches to the organization of polyvinyl chloride waste recycling processes are proposed. Originality. The principles of polyvinyl chloride processing based on the principles of the circular economy are proposed. Practical value. The data on the sources of polyvinyl chloride waste generation are systematized, and possible ways of their recycling are presented. The advantages and disadvantages of existing technologies and methods of PVC waste processing are analyzed. It is proposed to introduce a cyclic method of processing PVC waste by developing new and adjusting existing recipes for PVC compositions to increase the content of heat-stabilizing additives and the use of additives with prolonged effects.